2002
DOI: 10.5144/0256-4947.2002.336
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Community and Hospital-Based Long-Term Care Facilities in Saudi Arabia

Abstract: MH Mufti. A Case for Community and Hospital-Based Long-Term Care Facilities in Saudi Arabia. 2002; 22(5-6): 336-338 In countries like Saudi Arabia, where improvement in health and social status of the population has risen sharply in a short period of time, growth in the number of elderly persons is even more remarkable. Life expectancy at birth is currently 70 years, up almost 60% from 44 years in 1960. It is estimated that about 3% of the population of 18.3 million are over 65 years. 1The increasing deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There is also a limited response to older people’s care in acute care hospitals in Saudi Arabia. Similarly, one study claims that hospitals are not ideal for older persons with long-term conditions who have high accident rates (62.5%) that primarily occur in patients aged 60 years or older 6 ) . It is suggested that may be the result, in part, to nursing staff lacking the time and skills necessary to provide longer-term hospital care for older patients 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…There is also a limited response to older people’s care in acute care hospitals in Saudi Arabia. Similarly, one study claims that hospitals are not ideal for older persons with long-term conditions who have high accident rates (62.5%) that primarily occur in patients aged 60 years or older 6 ) . It is suggested that may be the result, in part, to nursing staff lacking the time and skills necessary to provide longer-term hospital care for older patients 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…We were particularly interested in participants who were literate, because the probes used in this fieldwork involve some reading and writing. Likewise, we recruited individuals living at home because generally, older Saudis live with their families in the same household and prefer informal home care [12,13].…”
Section: Participants and Recruitmentmentioning
confidence: 99%